Veronderstelt de natuur een plan en intelligentie?Veronderstelt de natuur een plan en intelligentie? - Vroom, Hendrik M. (Verbum et ecclesia, 2007)
This contribution analyses the various domains of argumentation in the discussions on intelligent design and creation & evolution: scientific facts, philosophical interpretations on nature and on divinity, and theological reflections upon the relation between and integration of such philosophical interpretations and the biblical message about God. If arguments from those domains are related to quickly, the argumentation becomes sloppy and conclusions are reached to hasty. Therefore the different domains have been distinguished carefully. The intelligence of natural laws points to an intelligent source. The complexity of progress in the evolutionary process suggests that it is improbable that it just has developed by change - whatever the consequences for the understanding of developments that can be valuated as good or as evil. In the last sections the relation between a philosophical idea of intelligence and creation and the biblical ideas of God as Creator , of the goodness of God, and the reality of evil are discussed.